Linkage to and engagement in HIV care in western Kenya: an observational study using population-based estimates from home-based counselling and testing. Issue 1 (January 2015) - Genberg, Becky L; Naanyu, Violet; Wachira, Juddy; Hogan, Joseph W; Sang, Edwin; Nyambura, Monicah; Odawa, Michael; Duefield, Corey; Ndege, Samson; Braitstein, Paula
Summary: Background: Few population-based studies exist on the HIV care continuum in sub-Saharan Africa. We aimed to describe engagement in care in all adults with an existing diagnosis of HIV and to assess the time to and predictors of linkage and engagement in adults newly diagnosed via home-based counselling and testing (HBCT) in a high-prevalence setting in western Kenya. Methods: Data were derived from AMPATH (Academic Model Providing Access to Healthcare), which has provided HIV care in western Kenya since 2001 and the HBCT programme, which has been operating since 2007. After a widespread HBCT programme in Bunyala subcounty from December, 2009, to February, 2011, we reviewed electronic medical records to identify uptake of care in individuals (aged 13 years or older) with previously known (self-reported) infection and new (identified at HBCT) HIV diagnoses as of June 1, 2014. We defined engagement in HIV care as an initial encounter with an HIV care provider. We used Cox regression analysis to examine the predictors of engagement in care for newly diagnosed individuals. Findings: Of the 3482 adults with HIV identified at HBCT, 2122 (61%) had previously been diagnosed with HIV, of whom 1778 (84%) had had at least one clinical encounter within AMPATH. 993 (73%) of the 1360 individuals with new diagnoses at HBCT were registered in the electronic medical records, although only 209 (15%) had seen a clinician over a median of 3·4 years since diagnosis. The median time to engagement in the newly diagnosed individuals was 60 days (IQR 10–411). Interpretation: Creative and innovative strategies are needed to support people to engage with care when they are newly diagnosed with HIV through population-based case-finding initiatives. Funding: US President's Emergency Plan for AIDS Relief (PEPFAR), Abbott Laboratories, thePurpleville Foundation, theGlobal Business Coalition, theUS National Institute of Mental Health, and theBill & Melinda Gates Foundation .